BDE99 (2,2′,4,4′,5-PENTABROMODIPHENYL ETHER) SUPPRESSES DIFFERENTIATION INTO NEUROTRANSMITTER PHENOTYPES IN PC12 CELLS - Slotkin, Theodore A. (2013)
Early-life exposures to brominated diphenyl ethers (BDEs) lead to neurobehavioral abnormalities later in life. Although these agents are thyroid disruptors, it is not clear whether this mechanism alone accounts for the adverse effects. We evaluated the impact of 2,2′,4,4′,5-pentabromodiphenyl ether (BDE99) on PC12 cells undergoing neurodifferentiation, contrasting the effects with chlorpyrifos, a known developmental neurotoxicant. BDE99 elicited decrements in the number of cells, evidenced by a reduction in DNA levels, to a lesser extent than did chlorpyrifos. This did not reflect cytotoxicity from oxidative stress, since cell enlargement, monitored by the total protein/DNA ratio, was not only unimpaired by BDE99, but was actually enhanced. Importantly, BDE99 impaired neurodifferentiation into both the dopamine and acetylcholine neurotransmitter phenotypes. The cholinergic phenotype was affected to a greater extent, so that neurotransmitter fate was diverted away from acetylcholine and toward dopamine. Chlorpyrifos produced the same imbalance, but through a different underlying mechanism, promoting dopaminergic development at the expense of cholinergic development. In our earlier work, we did not find these effects with BDE47, a BDE that has greater endocrine disrupting and cytotoxic effects than BDE99. Thus, our results point to interference with neurodifferentiation by specific BDE congeners, distinct from cytotoxic or endocrine mechanisms.